2012
DOI: 10.1016/j.foodres.2011.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Exopolysaccharide-producing Bifidobacterium strains elicit different in vitro responses upon interaction with human cells

Abstract: Probiotic foods intended for human nutrition are gaining economic relevance but it is clear that for the application of new strains scientific and rational selection criteria must be used. In this work, the role of exopolysaccharide (EPS) produced by Bifidobacterium strains in their potential beneficial effect was studied. Two in vitro biological models were used to test the interaction of seventeen strains and their polymers with the host. In general, the EPS-producing bifidobacteria showed good adherence pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
73
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 49 publications
4
73
0
2
Order By: Relevance
“…lactis DSM10140 and derivative strains was studied with the epithelial intestinal cell line HT29, derived from human colon adenocarcinoma. The cell line maintenance, culture conditions, and reagents were described elsewhere (27). For the adhesion experiments, 10 5 cells ml Ϫ1 were seeded in 48-well plates and incubated to confluence (monolayer of approximately 10 7 cells ml Ϫ1 ), at about 13 days.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…lactis DSM10140 and derivative strains was studied with the epithelial intestinal cell line HT29, derived from human colon adenocarcinoma. The cell line maintenance, culture conditions, and reagents were described elsewhere (27). For the adhesion experiments, 10 5 cells ml Ϫ1 were seeded in 48-well plates and incubated to confluence (monolayer of approximately 10 7 cells ml Ϫ1 ), at about 13 days.…”
Section: Methodsmentioning
confidence: 99%
“…lactis DSM10140 and derivative strains was determined using an in vitro model based on the cocultivation of human peripheral blood mononuclear cells (PBMCs) with the UV-irradiated strains in 48-well plates. The PBMCs were obtained as described by López et al (27). The UV-irradiated bacterial suspensions were prepared as described by López et al (28).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is also a common characteristic found in some bifido-EPS, but only a few papers have dealt with this research topic. Using an in vitro approach, López and coworkers (9) have analyzed the immune activity of EPS purified from 13 strains belonging to three Bifidobacterium species (B. animalis subsp. lactis, B. longum, and B. pseudocatenulatum).…”
Section: Bioactivity Of Eps From Bifidobacteriummentioning
confidence: 99%
“…Some EPS have been reported to act as virulence factors in several infectious diseases (3,4), but, in contrast, it has also been shown that bacterial EPS can have a positive impact on human health (5,6). Indeed, the production of EPS by some bacteria with probiotic traits has been tentatively correlated with their capability to modulate the host immune response, eliciting both innate and adaptive responses (7)(8)(9)(10). Additionally, EPS also help the producing bacteria, when they are ingested, to overcome gastrointestinal challenges and to persist for longer periods in the gut (8,11).…”
mentioning
confidence: 99%